Pengembangan Media Pembelajaran Interaktif pada Mata Pelajaran Dasar Desain Grafis Kelas X SMK Antartika 1 Sidoarjo - Ain , Moch. Ibnu; Astuti, Cindy Cahyaning (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2024)
This research was conducted at SMK Antartika 1 Sidoarjo, Department of Software Engineering. This research is a research and development. This study aims to produce adobe flash-based interactive learning media in the basic subjects of graphic design class X. This research use the ADDIE model which consists of 5 stages, namely (1) analysis; (2) design; (3) development; (4) implementation; (5) evaluation. The trial in this study involved media experts, material experts and small groups (10 students). The results of the value obtained from media experts get a percentage of 91% with the category "Very Eligible". The results of the assessment by material experts get a percentage of 95% with the category "Very Eligible". Small group trial with 10 students majoring in RPL got a percentage of 78.4% which was included in the "Eligible" category. The conclusion of this research is that interactive learning media based on Adobe Flash is very feasible to be used in teaching and learning activities.